1995
DOI: 10.1007/bf00004311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the molecular form of dietary nitrogen supply in sea bass larvae: Response of pancreatic enzymes and intestinal peptidases

Abstract: Sea bass (Dicentrarchus labrax) larvae were weaned at day 25 with microparticulated diets in which 10% of the nitrogen supply had different molecular forms: amino acid mixture (SLAA), casein hydrolysate (SLH) or fish meal (SLP). The control group (LP) was fed live prey. No difference was observed in larval growth between the weaned groups, but the survival was significantly higher in the SLH group. Trypsin secretion was stimulated in the SLAA group, whereas the SLH diet reduced the secretion from the exocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 27 publications
7
48
0
1
Order By: Relevance
“…In addition to the polyamine, free amino acids found in some diets might induce the increase in trypsin synthesis. Concerning the digestive contribution of diet, it is also suggested that live or artificial food does not contain trypsin activity [Cahu and Zambonino-Infante, 1995]. This is in agreement with the results displayed with PSA and PSI, which possess negligible enzymatic activities; there was no exogenous supply by the ingredients.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to the polyamine, free amino acids found in some diets might induce the increase in trypsin synthesis. Concerning the digestive contribution of diet, it is also suggested that live or artificial food does not contain trypsin activity [Cahu and Zambonino-Infante, 1995]. This is in agreement with the results displayed with PSA and PSI, which possess negligible enzymatic activities; there was no exogenous supply by the ingredients.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies showed that as the protein fraction increases in the diet of larvae, it can induce total proteolytic activities (Cahu and Zambonino Infante, 1995). In our trial, CP 53 had the higher protein level among the three formulated diets, and pepsin activity and mRNA amount were higher than larvae fed CP 43 during the experimental period.…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, the introduction of the casein mixture in a diet, alone or with fish meal, enhanced larval survival significantly. Previous experiments have suggested that this improvement may be due to hydrolysate fraction (Cahu and Zambonino Infante 1995). This beneficial effect of the casein hydrolysate has also been reported in the fresh water fish, Carassius auratus (Szlaminska et al 1991).…”
Section: Discussionmentioning
confidence: 62%